A Rare Case of Newly Acquired Hemophilia Following Diabetic Ketoacidosis in A Male Patient with IL-2 (Rs2069762) Polymorphism - Muhammad, Faizal; Arthareza, Adhelia Galuh Permatasari; Marwanta, Sri (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Diabetes is commonly linked to autoimmune processes, but acquired hemophilia A (AH)—a rare bleeding disorder due to factor VIII (FVIII) inhibitors—remains uncommon, particularly during diabetic ketoacidosis (DKA). Recent studies have suggested a role of IL-2 (rs2069762) polymorphism in FVIII inhibitor development. This study aims to highlight a rare case of newly acquired hemophilia coinciding with DKA and the presence of IL-2 gene polymorphism. Case Presentation: A 40-year-old male presented with dyspnea, abdominal pain, and signs of DKA. He had a history of drug-induced rash due to sulfasalazine. Initial management with IV fluids and insulin resolved the metabolic crisis. However, on day two, he developed spontaneous bruising and gross hematuria. Laboratory tests revealed a low FVIII inhibitor titer (1.2 BU) and positive insulin antibodies. Genetic testing showed TT homozygous polymorphism of IL-2 (rs2069762), potentially contributing to FVIII inhibitor formation. Results: The patient was treated with low-dose cyclophosphamide and methylprednisolone, followed by rituximab due to poor initial response. Intensive insulin therapy was also administered. After five weeks, clinical remission of AH was achieved, although the patient remains at risk for relapse due to the IL-2 polymorphism. Conclusion: This case illustrates a rare interplay between DKA and acquired hemophilia, potentially mediated by IL-2 (rs2069762) polymorphism. Prompt diagnosis and individualized immunosuppressive therapy are essential. The findings support further investigation into genetic predispositions in AH pathogenesis during autoimmune or metabolic stress events like DKA.